2012
DOI: 10.1093/abbs/gmr124
|View full text |Cite
|
Sign up to set email alerts
|

Human tetraspanin transmembrane 4 superfamily member 4 or intestinal and liver tetraspan membrane protein is overexpressed in hepatocellular carcinoma and accelerates tumor cell growth

Abstract: The human transmembrane 4 superfamily member 4 or intestinal and liver tetraspan membrane protein (TM4SF4/il-TMP) was originally cloned as an intestinal and liver tetraspan membrane protein and mediates density-dependent cell proliferation. The rat homolog of TM4SF4 was found to be up-regulated in regenerating liver after two-thirds hepatectomy and overexpression of TM4SF4 could enhance liver injury induced by CCl 4 . However, the expression and significance of TM4SF4/il-TMP in liver cancer remain unknown. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…TSPAN4 and Smoc2 were also upregulated in Shp Ϫ/Ϫ mice and fibrotic liver disease. A recent study showed that TSPAN4 was significantly overexpressed in HCC (22), and Smoc2 potentiates the angiogenic effects of growth factors (35). However, the functions of these genes in liver remain largely unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…TSPAN4 and Smoc2 were also upregulated in Shp Ϫ/Ϫ mice and fibrotic liver disease. A recent study showed that TSPAN4 was significantly overexpressed in HCC (22), and Smoc2 potentiates the angiogenic effects of growth factors (35). However, the functions of these genes in liver remain largely unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…In CCl 4 -induced acute liver injury model in rats, TM4SF4 is also up-regulated in injured livers, and overexpression of TM4SF4 can accelerate liver injury [10]. For humans, TM4SF4 is found to be overexpressed in 70% liver cancer tissues and correlates with tumor progression [11]. Moreover, TM4SF4 can regulate endocrine pancreas differentiation and directed cell migration [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to TM4SF1 and TM4SF5, which slightly increased cell proliferation in 2D cell culture condition, TM4SF4 had a slightly decreasing effect on cell growth. TM4SF4 is upregulated in injured liver in CCl 4 -treated mice [11], overexpressed in liver cancer tissues [12, 24], and is correlated with directional migration [16, 25], similar to TM4SF5 [26]. However, controversy surrounds the effects of TM4SF4 on cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TM4SF1 in breast cancer cells couples the collagen I receptor tyrosine kinase DDR1 to the syntenin 2, a cortical adaptor, and further PKCα that promotes phosphorylation and activation of JAK2 and STAT3 for cancer stem cell traits and metastatic reactivation in the metastatic sites such as lung, bone, and brain [8]. Meanwhile, TM4SF4 is expressed in non-dividing hepatocytes and upregulated during liver injury possibly for cellular differentiation and regeneration [911], although it is highly enhanced in liver cancer [12]. Enhanced TM4SF4 level in lung carcinoma cells can lead to resistance to radiotherapy via IGF1-induced IGFR activation [13].…”
Section: Introductionmentioning
confidence: 99%